The Situation After Divorce: Fathers and Children. Issue 2 (3rd March 2016) - Shevchenko, I.O.
Abstract : The artricle analyzes the relationship between fathers and children after the parents' divorce, identifying the following conditions that influence their relationship: the child's age at the time of divorce, the behavior of the child and other relatives, the father's desire to participate in the child's life, the place of residence, and the father's career. Three stages of development in this relationship are identified, and the types of paternal behavior during and after the divorce are clarified. Special attention is focused on the child's socialization after the divorce and the implications of this for socialization in contemporary circumstances.